The Role of Aspirin in the Management of Intracranial Aneurysms: A Systematic Review and Meta-Analyses - Yang, Shuwen; Liu, Tianyu; Wu, Yuehui; Xu, Nina; Xia, Liangtao; Yu, Xinyu (Frontiers in Neurology, 2021)
Objective To evaluate the association between aspirin use and the risks of unruptured intracranial aneurysm (UIA) growth and aneurysmal subarachnoid hemorrhage (aSAH). Methods We searched PubMed and Scopus from inception to 1 September 2020. Studies evaluating the associations between aspirin prescription and the risk of UIA growth or the risk of aSAH were included. The study only included patients with intracranial aneurysms. We assessed the quality of included studies using the Newcastle-Ottawa scale. Random-effects meta-analysis was conducted to pool the estimates of effect size quantitatively. Sensitivity analyses using the leave-one-out strategy were performed to identify any potential source of heterogeneity. Results After a review of 2226 citations, five cohort studies, two case-control studies, and one nested case-control study involving 8898 participants were included. Pooled analyses showed that aspirin use, regardless of frequency and duration, was associated with a statistically significantly lower risk of UIA growth (OR 0.25, 95% CI 0.11-0.54; I2=0.0%, p=0.604) and aSAH (OR, 0.37, 95%CI, 0.23-0.58; I2=79.3%, p=0.001) in patients presented with intracranial aneurysms. The results did not significantly change in sensitivity analyses. Conclusions Summarizing available evidence in the literature, our findings indicate that aspirin use, regardless of frequency and duration, was associated with a statistically significantly lower risk of UIA growth and aSAH in patients with UIA. Well-designed and large-scale clinical trials are needed to help define the role of aspirin as a protective pharmaceutical for UIAs.